2020
DOI: 10.1155/2020/7573491
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes and Prediabetes among Children Aged 11-14 Years Old in Vietnam

Abstract: Aim. Diabetes in children is becoming more prevalent in some countries. However, in most countries, little is known about the epidemiology of this disease. This study is aimed at estimating the prevalence of type 1 and type 2 diabetes and prediabetes among children in Vietnam and examining factors associated with the conditions. Methods. A total of 2880 students aged 11-14 years old were recruited for the survey, using a school-based and nationally representative sampling frame. Capillary blood samples of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…This finding is consistent with previous studies 18–20 showing that obesity may be a risk factor for prediabetes, although one study found no relationship between obesity and prediabetes 21 . The finding of a lower prevalence of prediabetes in rural areas compared with that in urban areas in this study is consistent with published data in China 22 and Vietnam 23 . Aging and growing obesity levels that accompany urbanization may therefore represent precursors to a global prediabetes epidemic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previous studies 18–20 showing that obesity may be a risk factor for prediabetes, although one study found no relationship between obesity and prediabetes 21 . The finding of a lower prevalence of prediabetes in rural areas compared with that in urban areas in this study is consistent with published data in China 22 and Vietnam 23 . Aging and growing obesity levels that accompany urbanization may therefore represent precursors to a global prediabetes epidemic.…”
Section: Discussionsupporting
confidence: 91%
“…21 The finding of a lower prevalence of prediabetes in rural areas compared with that in urban areas in this study is consistent with published data in China 22 and Vietnam. 23 Aging and growing obesity levels that accompany urbanization may therefore represent precursors to a global prediabetes epidemic. In another study, prevalence of IFG was 88% for those with family history compared to 1.9% for those without, 24 similar to our study and the Cameron County Hispanic Cohort data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the prevalence of T2DM in children with obesity was 18.3% in China [28] and 12.6% to 24.6% in other countries. [29][30][31][32] Thus, our findings of a high rate of glucose metabolism disorder in children with obesity are broadly in agreement with the results of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…In Vietnam, a previous publication revealed that a high number of T1D cases presenting with diabetic ketoacidosis in young adults are negative for pancreatic ICAs. Additionally, although the authors reported a low prevalence of T1D and T2D among children aged 11–14 years (1.04), there has been a lack of prevalence rates published for T1D and T2D in younger children and descriptions of autoimmune markers [ 16 ]. The lower frequency of ICAs in children with T1D onset before five years of age may be due to a more rapid disappearance of islet cell antigens than in patients with a later onset [ 13 ].…”
Section: Introductionmentioning
confidence: 99%